2019
DOI: 10.1108/ict-11-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an organisational commitment instrument for generation Y employees in small and medium-sized enterprises in Thailand

Abstract: Purpose Organisational commitment (OC) has become a hot behavioural topic among researchers, scholars and consulting firms. However, OC instruments have rarely been studied and developed by academics in small and medium-sized Thai enterprises (SMEs). The purpose of this paper is to develop an instrument to measure the OC of Generation Y employees in Thai SMEs. Design/methodology/approach A measurement scale for OC was established in three stages. First, 16 questions were developed as a questionnaire based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Organizational commitment, along the leadership plays a significant factor in determining organizational long term success. The recent studies have examined organizational commitment’s role (Keskes et al , 2018; Na-nan and Saribut, 2019; Ramalho Luz et al , 2018), and confirmed its inevitable role in organizational effectiveness. Moreover, organizational commitment and job satisfaction have been affected by transformational leadership, which is reflected in positive job performance of employees (Al-Amin, 2017; Aliyana and Muzzaki, 2019).…”
Section: Literature Reviewmentioning
confidence: 86%
“…Organizational commitment, along the leadership plays a significant factor in determining organizational long term success. The recent studies have examined organizational commitment’s role (Keskes et al , 2018; Na-nan and Saribut, 2019; Ramalho Luz et al , 2018), and confirmed its inevitable role in organizational effectiveness. Moreover, organizational commitment and job satisfaction have been affected by transformational leadership, which is reflected in positive job performance of employees (Al-Amin, 2017; Aliyana and Muzzaki, 2019).…”
Section: Literature Reviewmentioning
confidence: 86%
“…This implies the importance of these factors and educators and researchers should pay attention to AV and PT when explaining EE. EE is also necessary for explaining the phenomenon of IWB since EE is a psychological perception which manifests as dedication and work integration of employees [31,[91][92][93][94]. When they possess work engagement, employees are ready to create innovative ways of working to make their jobs more effective.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…First, the questionnaires may be affected by individual bias of participants as a consequence of cross-sectional and self-reported data. Aguinis et al (2001), Na-Nan et al (2018b) and Na-Nan and Saribut (2019) stated that social researchers should be aware of and recognise that language, culture, technology and economics can all affect the quality of data collection. When conducting surveys, researchers should be aware that language and context can affect questionnaire validation and research findings.…”
Section: Limitations and Future Researchmentioning
confidence: 99%